ANALYSIS OF THE DIFFERENCE IN WAGES FOR RICE CUTTING BETWEEN MEN AND WOMEN FROM THE PERSPECTIVE OF UJRAH BI AL-'AMAL - Badrul Munir; Nurmakrufiana (JURISTA: Jurnal Hukum dan Keadilan, 2019)
Wages represent rewards or services. In addition to being a form of muamalah, wages are something that many individuals do to earn a livelihood. In addition to purchasing and selling transactions, cooperative transactions also involve wages, as in the case of cooperation between rice field owners and workers. The author of this study refers to the remuneration for paddy cutting services (cooperation wages) in the village of Teureubeuh, located in Jantho, Aceh Besar. In other words, the communities of Teureubeuh village, Jantho, Aceh Besar, continue to use the practise of wages, which dates back to antiquity and provides labourers with remuneration for the services rendered. Conversely, a wage disparity emerged between male and female labourers in Teureubeuh village, Jantho Aceh Besar, with the former receiving a higher remuneration for paddy cutting. The present study investigates three inquiries: To begin with, what wage payment system is in place for rice cutting between males and women in Gampong Teureubeuh, Jantho, Aceh Besar? Furthermore, what are the determinants influencing wage distribution between males and females in Gampong Teureubeuh, Jantho, Aceh Besar? Furthermore, from an ujrah bi al-'amal standpoint, what is the significance of the wage disparity in paddy cutting between male and female labourers? Based on the conducted research, it can be inferred that the wage disparity in rice cutting between male and female labourers, as assessed through the lens of ujrah bi al-amal, is permissible under Islamic law. This is supported by the observation that male labourers operate at a faster pace than their female counterparts and employ a more robust and rapid grip when slicing rice, in contrast to the slower pace of rice cutting by female labourers.